Topological Structures of Derivative Weighted Composition Operators on the Bergman Space. (18th November 2015) - Tong, Ce-Zhong; Yuan, Cheng; Zhou, Ze-Hua
Abstract : We characterize the difference of derivative weighted composition operators on the Bergman space in the unit disk and determine when linear-fractional derivative weighted composition operators belong to the same component of the space of derivative weighted composition operators on the Bergman space under the operator norm topology.